Sanitary milk for city consumption - Zimmerman, Frederick (My University, 1898)
Introduction: The first thing to consider in the production of sanitary milk is the stock. All animals should be free from the slightest trace of disease; they should be tuberculin tested, as this is the only certain way to detect this dread disease; one seventh of all people die of tuberculosis, or consumption as it is called in man. Tuberculosis of cattle is communicable to man through effected milk; and all cattle are liable to be effected; the Kansas Experiment Stations purchased 20 common cows in western Kansas, and had them tested for tuberculosis; the State Veterinarian, Dr. Fisher, had not the slightest ground for suspecting tuberculosis, yet 20% of them were shown to be effected; if these cows were diseased when they were kept in the pen all their lives, what could be expect of city cows that live in filth?
Citation: Zimmerman, Frederick. Sanitary milk for city consumption. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Cows; Milk; Tuberculosis; Sanitation; Disease; Theses; Manuscripts (documents)